Réponses

Meilleure réponse !
2012-10-17T00:14:52+02:00

f(x)=x³-30x²+112

f(2)=2³-30(2²)+112=8-30*4+112=8-120+112=0 => x=2 est solution de f(x)

d'où f(x)=(x-2)(ax²+bx+c)=ax³+bx²+cx-2ax²-2bx-2c=ax³+(b-2a)x²+(c-2b)x-2c

f(x)=ax³+(b-2a)x²+(c-2b)x-2c=x³-30x²+112

d'où a=1, b-2a=-30, c-2b=0, -2c=112

a=1

b=-30+2a=-30+2*1=-30+2=-28

-2c=112 => c=-112/2=-56

vérification : c-2b=0 => -56-2(-28)=-56-(-56)=-56+56=0 OK

donc f(x)=(x-2)(x²-28x-56)

x²-28x-56 est de la forme ax²+bx+c=0

∆=b²-4ac=(-28)²-4(1)(-56)=784+224=1008=(12√7)² donc ∆>0 => 2 solutions x₁ et x₂

x₁=(-b-√∆)2a=(-(-28)-12√7)/(2(1))=(28-12√7)/2=14-6√7

x₂=(-b+√∆)2a=(-(-28)+12√7)/(2(1))=(28+12√7)/2=14+6√7

x²-28x-56=(x-14+6√7)(x-14-6√7)

donc f(x)=(x-2)(x-14+6√7)(x-14-6√7) d'où pour f(x)=0 on a 3 solutions

f(x)=0, S={14-6√7, 2, 14+6√7}